2014 IEEE International Electric Vehicle Conference (IEVC) 2014
DOI: 10.1109/ievc.2014.7056208
|View full text |Cite
|
Sign up to set email alerts
|

Power tracking with maximum efficiency for wireless charging of E-bikes

Abstract: Wireless charging techniques, based on Inductive Power Transfer (IPT), are attractive for Electric Vehicles (EV), due to benefits such as convenience and safety. An accurate valuation of the maximum achievable efficiency in an IPT system is extremely unlikely due to the high sensitivity to parasitic elements variations. Therefore, an �on site� procedure of power efficiency characterization is useful to get a precise description of the efficiency curve and obtain the actual maximum efficiency. In this paper, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The MEPT principle is important to WPT for both low-power applications due to the large quantities of portable electronic devices and high-power applications due to high power consumption. In 2014, five research publications reported independent investigations on various ideas of tracking optimal load or tracking maximum efficiency operations [7]- [11]. Interestingly, three references [7]- [9] appeared online in August 2014 and as printed versions in the same 2015 issue of the IEEE Transactions on Power Electronics.…”
Section: A Basic Principles Of Maximum Efficiency Point Tracking (Mept)mentioning
confidence: 99%
See 1 more Smart Citation
“…The MEPT principle is important to WPT for both low-power applications due to the large quantities of portable electronic devices and high-power applications due to high power consumption. In 2014, five research publications reported independent investigations on various ideas of tracking optimal load or tracking maximum efficiency operations [7]- [11]. Interestingly, three references [7]- [9] appeared online in August 2014 and as printed versions in the same 2015 issue of the IEEE Transactions on Power Electronics.…”
Section: A Basic Principles Of Maximum Efficiency Point Tracking (Mept)mentioning
confidence: 99%
“…For this reason, any WPT operation based on the maximum power theorem or impedance matching with a source impedance of 50Ω cannot achieve energy efficiency higher than 50%. Since [7]- [11] were published, there are over 50 MEPTrelated research publications from 2015-2022 according to IEEE Xplore. Some of these publications with different implementation approaches will be highlighted in the following discussion.…”
Section: A Basic Principles Of Maximum Efficiency Point Tracking (Mept)mentioning
confidence: 99%
“…Moreover, it's worth remembering that one of the most elements of a MOSFET producing switching diode, which is traversed by current reverse recovery time. This interval time is Definition of reverse recovery time [28] in fact, both for diodes and , this charge, called reversed recovery I d (t)dt (10) urn-off power losses are [28]:…”
Section: Analysis Of the Isolated Convertermentioning
confidence: 99%
“…Because of their great thermal conductivity and wide bandgap, these ones can be exploited to get high power and to operate at high temperatures. These are the reasons why SiC plays an important role in the implementation of new technology applications, such as high efficiency DC-DC converters, DC-AC converters, inverters for solar and wind energy, photo-voltaic converters, power converters for electrical and vehicles, motor drives, power inverters for industrial equipment, high voltage switches for X-ray generators, thin-film coating processes, chargers and power supplies for renewable energy systems [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Many power devices are produced, such as Schottky barrier diodes, MOSFETs, power modules, IGBTs, BJTs, and many companies are engaged in making them.…”
Section: Introductionmentioning
confidence: 99%
“…The problems can be solved by wireless charging systems with convenience and can save people from the tiresome plugging action. Therefore, the wireless power transfer (WPT) technique for EB chargers has been studied for a few years [2][3][4][5], and the wireless charging market has been growing rapidly for a couple of years.…”
Section: Introductionmentioning
confidence: 99%